Determinants of Dual Enrollment Access: A National Examination of Institutional Context and State Policies - George Spencer; Mónica Maldonado (SAGE Publishing, 2021)
Despite considerable growth in rates of participation in recent years, concerns remain about disparities in access to dual enrollment programs. On one hand, there are questions regarding who has access, which students are most disadvantaged, and which schools fail to offer the opportunity at all? On the other hand, there has been little clarity about what helps to improve access-in particular, what is the role of state policies in this effort? Using nationally representative data sources, this study uses a multilevel approach to understand how dual enrollment participation varies at the level of states, schools, and students. The findings reveal that policy mandates are among the strongest predictors of dual enrollment participation. Furthermore, schools serving greater proportions of racially minoritized students are the least likely to offer dual enrollment, but within schools, students from lower socioeconomic backgrounds have a lower probability of participating relative to their more affluent peers.